A Case of Thymoma-Myasthenia Gravis in an Adult Malaysian Patient with Anterior Mediastinal Lesion - Alakhali, Khaled Mohammed; Mahdi, Yasameen Mohammed; Irawati, Lyna; Mahuob, Abdulaleem (Journal of Pharmacy Practice and Community Medicine)
Myasthenia Gravis (MG) is a neuromuscular junction disease. Around fifteen percent of myasthenia gravis patients are found to have thymoma and 20%-25% of thymoma patients have myasthenia gravis. T-MG is equally common of both men and women. It happens at any age, with a 50-year peak start. Asians, Pacific Islanders and African Americans have a greater chance of contracting this disease. Thymomatous myasthenia gravis tends to be clinically difficult; with poor prognosis. We reported a 58-year-old Chinese woman who wasadmitted to a public hospital with complaints of fever, tachycardia, nausea and chills. She has a history of MG and hyperlipidemia. In 2014, she had thymoma and underwent thymectomy. Five years later, she was diagnosed withrecurrent thymomastage IIIB and prescribed with combination chemotherapy of cyclophosphamide, doxorubicin and cisplatin. After receiving the first cycle of the chemotherapy regimen, she developed febrile neutropenia and thrombocytopenia. In conclusion, MG has a complicated clinical course and poor prognosis. Nevertheless, early aggressive treatment could improve the patient outcomes.
Keywords: Myasthenia gravis; Thymoma; Thymectomy; Adult Patient; Malaysian.